Dental adhesive composition containing a chain transfer agent

By incorporating α-alkylstyrene compounds as radical chain transfer agents, the dental adhesive composition addresses issues of polymerization shrinkage stress and mechanical strength, achieving durable and long-lasting adhesion in dental applications.

JP7649619B2Active Publication Date: 2025-03-21SHOFU INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2019048084
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-20
Filing Date
2019-03-15
Publication Date
2025-03-21
Estimated Expiration
2039-03-15

AI Technical Summary

Technical Problem

Existing dental adhesive compositions face challenges in achieving durable adhesive properties, high mechanical strength, and resistance to polymerization shrinkage stress, especially when used in deep cavities.

Method used

Incorporating an α-alkylstyrene compound as a radical chain transfer agent in the dental adhesive composition to reduce polymerization shrinkage stress while maintaining high mechanical properties and durability.

Benefits of technology

The use of α-alkylstyrene compounds effectively delays the gelation point during polymerization, reducing polymerization shrinkage stress and enhancing the durability and adhesion of the dental adhesive composition, even in bulk fill applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649619000001
    Figure 0007649619000001
  • Figure 0007649619000002
    Figure 0007649619000002
  • Figure 0007649619000003
    Figure 0007649619000003
Patent Text Reader

Abstract

To provide a 1 paste type dental adhesive composition comprising mechanical property and aesthetic property which are required for a restoration material, excellent in durable adhesive strength to a dentine, hardly receiving affection of polymerization shrinkage stress even when being filled and cured collectively, and exhibiting preferable durable adhesion.SOLUTION: There is provided a dental adhesive composition comprising: (a) a polymerizable monomer including no acidic group; (b) a polymerizable monomer including an acidic group; (c) a filler; (d) a photoinitiator; (e) a chain transfer agent, in which the chain transfer agent includes α-alkylstyrene compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to dental adhesive compositions used in the dental field, such as dental adhesives, dental self-adhesive composite resins, dental self-adhesive core build-up materials, dental resin cements, dental self-adhesive surface coating materials, dental self-adhesive pit and fissure sealants, and dental self-adhesive nail varnishes. [Background technology]

[0002] In clinical dentistry, dental composite resin fillings are used to restore the aesthetics and function of teeth that have been lost due to caries, fractures, etc. In general, dental composite resin fillings are prepared by mixing a resin matrix made of several types of polymerizable monomers, various fillers such as inorganic fillers and organic-inorganic composite fillers, and a polymerization initiator to form a uniform paste. Requirements for composite resins for dental fillings include high mechanical strength to withstand occlusal pressure, color and light transparency similar to that of natural teeth, low polymerization shrinkage to suppress the occurrence of contraction gaps during polymerization and hardening, maintenance of surface smoothness and luster when polished, high X-ray contrast to facilitate prognosis diagnosis, sustained release of various ions such as fluoride to strengthen tooth substance and suppress secondary caries, and excellent operability when dentists perform filling operations.

[0003] Among composite resins, a bulk-fill type composite resin has appeared, which has a high light-curing depth and reduced polymerization shrinkage. This type has a higher light-curing depth than conventional composite resins, and can be filled and cured in one go without layering for deep and large cavities, shortening the time required for filling and light irradiation, and reducing the burden on the surgeon and patient. However, by filling and curing in one go, the volume polymerization shrinkage that occurs during polymerization and the polymerization shrinkage stress on the cavity wall are significantly increased compared to when layering and curing is performed, and concerns remain about the formation of contraction gaps during polymerization and the resulting secondary caries. In particular, when the composite resin is cured using a high-power light irradiator, which has recently become widely used, the polymerization proceeds rapidly, and the polymerization shrinkage stress of the composite resin tends to increase in proportion to the light irradiation intensity.

[0004] Recently, one-paste type self-adhesive composite resins have also appeared. These self-adhesive composite resins have adhesive properties to enamel and dentin by themselves, so they do not require bonding procedures with bonding agents as with conventional composite resins, and can be easily restored. Furthermore, self-adhesive composite resins can be restored simply by filling the cavity and curing it, so it is possible to eliminate the effects of technical errors made by the surgeon during adhesive restoration, such as insufficient air drying during bonding procedures with bonding agents and control of the thickness of the coating layer of bonding agents, and it is expected that more reliable restorations with fewer errors will be possible. However, in order to ensure sufficient adhesive strength, it was necessary to incorporate a certain amount of the acidic group-containing polymerizable monomer contained in the resin component in order to develop the adhesiveness of the self-adhesive composite resin to the tooth structure. In other words, when the amount of inorganic filler is increased to improve the mechanical properties of the self-adhesive composite resin, the adhesiveness tends to decrease, and there is a trade-off between these two. Therefore, in order to ensure adhesiveness, it is necessary to ensure a certain amount of resin content, which results in an increase in polymerization shrinkage due to polymerization hardening of the resin component, and a problem occurs in that the adhesive strength decreases due to the generation of polymerization shrinkage stress in the pulling direction that peels off from the tooth structure at the adhesive interface with the tooth structure. For this reason, the current situation is that self-adhesive composite resins are required to have stable and durable adhesiveness over the long term.

[0005] Furthermore, in the case of self-adhesive bulk-fill type composite resins that combine a one-paste type self-adhesive composite resin with a high light-curing depth, in addition to the occurrence of polymerization shrinkage stress associated with a certain amount of resin content as described above, there is an increase in polymerization shrinkage stress due to the light-curing all at once, making it extremely difficult to obtain stable, durable adhesive strength to tooth structure over the long term.

[0006] Patent Document 1 reports a technique of blending a photocleavable polymerizable monomer in order to reduce the polymerization shrinkage stress of a composite resin. These photocleavable polymerizable monomers are said to be capable of reducing the volume polymerization shrinkage and polymerization shrinkage stress by cleaving a part of the crosslinked network of the polymer formed by polymerization. However, if the blending amount of the photocleavable polymerizable monomer is increased too much, there is a problem that it leads to an increase in viscosity and a decrease in mechanical properties.

[0007] Patent Document 2 also reports a technique of adding a polymerizable stable radical to reduce the polymerization shrinkage stress of a composite resin. It is said that these radical chain transfer agents can reduce the polymerization shrinkage stress by delaying the gel point during polymerization. However, according to the results of the inventors' investigation, it was confirmed that the effect of reducing the polymerization shrinkage stress by adding a polymerizable stable radical is poor, and that the photocuring depth tends to decrease significantly when the amount of the added radical is increased.

[0008] Patent Document 3 proposes a technique of blending an α-alkylstyrene compound with a photopolymerization initiator composition of a high-speed polymerization system that combines an α-diketone compound, an amine compound, and a photoacid generator. When a polymerizable composition containing the photopolymerization initiator of the high-speed polymerization system is filled into a cavity, the rapid polymerization shrinkage stress accompanying the high-speed polymerization reaction acts on the interface between the polymerized hardened body and the cavity, and a contraction gap is likely to occur. This document reports that blending an α-alkylstyrene compound with the photopolymerization initiator of the high-speed polymerization system suppresses the polymerization shrinkage stress and obtains a polymerized hardened body that has both excellent cavity wall compatibility and mechanical strength. However, this document describes that the effect is expressed by combining an α-alkylstyrene compound with a high-speed polymerization system, and that when an α-alkylstyrene compound is blended with a conventional general photopolymerization initiator system consisting of an α-diketone compound and an amine compound, sufficient mechanical strength and cavity wall compatibility cannot be obtained. In addition, the adhesiveness to tooth structure was not taken into consideration, and the effect on them was unknown.

[0009] As described above, there was no one-paste type dental adhesive restorative material that had the mechanical properties and aesthetics required for filling and restorative materials, was not susceptible to the effects of polymerization shrinkage stress, and had excellent durable adhesive strength to tooth structure. Furthermore, when these restorative materials were filled and light-cured at the same time, the durable adhesive strength was not clinically sufficient, and technical issues remained. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Special Publication No. 2009-539861 [Patent Document 2] Special Publication No. 2016-532640 [Patent Document 3] JP 2016-169180 A Summary of the Invention [Problem to be solved by the invention]

[0011] The object of the present invention is to provide a dental adhesive composition for use in the dental field, such as a dental adhesive, a dental self-adhesive composite resin, a dental self-adhesive abutment construction material, a dental resin cement, a dental self-adhesive surface coating material, a dental self-adhesive pit and fissure sealant, a dental self-adhesive manicure material, etc., which has a durable adhesiveness capable of stably adhering to biological hard tissues (tooth enamel and dentin) for a long period of time, high mechanical properties capable of withstanding occlusal pressure, and an excellent color compatibility capable of being used for aesthetic restoration. Furthermore, the dental adhesive restorative material of the present invention is characterized by having a good durable adhesiveness capable of being used without causing clinical problems such as detachment, even when it is filled and cured in a deep and large cavity all at once. [Means for solving the problem]

[0012] As a result of intensive research to achieve the above object, the present inventors have found that the above problem can be solved by including an α-alkylstyrene compound as a radical chain transfer agent in a photocurable restorative material having self-adhesive properties, and have arrived at the present invention. That is, by including an α-alkylstyrene compound as a chain transfer agent, it is possible to reduce polymerization shrinkage stress while maintaining high curability, and it is possible to provide a self-adhesive restorative material that does not decrease in mechanical properties as a restorative material or durable adhesion to tooth structure. Furthermore, by making the refractive index of the polymerizable component before curing relatively close to the refractive index of the filler, the restorative material of the present invention has high transparency before curing, and can also be imparted with a deep photocuring depth that allows large, deep cavities to be filled and cured all at once. The restorative material of the present invention exhibits long-term stable durable adhesion to tooth structure even when it is a bulk fill type that is easily affected by such polymerization shrinkage stress.

[0013] The mechanism by which the dental adhesive composition of the present invention exhibits such excellent effects is not clear, but it is presumed to be due to the following reasons. In general, radical chain transfer agents temporarily receive radicals from polymer chains grown by radical polymerization, and stop the growth of the polymer. Then, they have the property of attacking the monomer again to form radicals of the monomer, and then starting the polymerization again. That is, by temporarily stopping the polymer growth in this way, they exhibit the function of delaying the formation of a polymer network (gelation point) during polymerization. However, due to this property, when the amount of chain transfer agent added increases, the function of stopping the polymer growth becomes stronger, and it tends to function as a polymerization inhibitor, leading to a decrease in the polymerization rate. However, it has been revealed that, among radical chain transfer agents, α-alkylstyrene compounds not only have an excellent effect of delaying the gelation point, but also have excellent properties such as being less likely to cause a decrease in the polymerization rate. Furthermore, α-alkylstyrene compounds maintain these properties even after long-term storage at room temperature, and have a major advantage in that they have excellent storage stability compared to other chain transfer agents. Due to such notable advantages of the α-alkylstyrene compound, it is believed that the dental adhesive composition of the present invention exhibits significantly reduced polymerization shrinkage stress, and exhibits high mechanical properties and excellent durable adhesion.

[0014] That is, the present inventors provide the following invention in this application. (a) a polymerizable monomer not containing an acidic group, (b) acidic group-containing polymerizable monomer, (c) filler; (d) a photopolymerization initiator, (e) a chain transfer agent, In a dental adhesive composition comprising: (e) A dental adhesive composition, wherein the chain transfer agent comprises an α-alkylstyrene compound. Effect of the Invention

[0015] The present invention relates to a one-paste type dental adhesive composition that has the mechanical properties and aesthetics required for a restorative material and has excellent durable adhesive strength to tooth structure. Furthermore, the composition of the present invention is less susceptible to the effects of polymerization shrinkage stress even when filled and cured all at once, and exhibits good durable adhesiveness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Each component of the dental adhesive composition containing the chain transfer agent of the present invention will be described in detail below. <(a) Acidic Group-Free Polymerizable Monomer> The (a) acidic group-free polymerizable monomer that can be used in the present invention can be any known monofunctional and / or polyfunctional polymerizable monomer that does not have an acidic group and is generally used in the dental field. A representative example of a generally suitable polymerizable monomer is a (meth)acrylate monomer or a (meth)acryloyl polymerizable monomer that has an acryloyl group and / or a methacryloyl group. In the present invention, (meth)acrylate or (meth)acryloyl is used to collectively refer to both an acryloyl group-containing polymerizable monomer and a methacryloyl group-containing polymerizable monomer.

[0017] Specific examples of (meth)acrylate polymerizable monomers that can be used as the (a) acidic group-free polymerizable monomer are as follows: Examples of monofunctional monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate, i-butyl (meth)acrylate), hexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and allyl (meth)acrylate. Examples of the suitable monomer units include (meth)acrylic acid esters such as 2-ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, glycerol (meth)acrylate, and isobornyl (meth)acrylate; silane compounds such as γ-(meth)acryloyloxypropyltrimethoxysilane and γ-(meth)acryloyloxypropyltriethoxysilane; and nitrogen-containing compounds such as 2-(N,N-dimethylamino)ethyl (meth)acrylate, N-methylol (meth)acrylamide, and diacetone (meth)acrylamide.

[0018] Examples of aromatic bifunctional monomers include 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxy phenyl)propane, 2(4-(meth)acryloyloxyethoxyphenyl)-2(4-(meth)acryloyloxydiethoxyphenyl)propane, 2(4-(meth)acryloyloxydiethoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2(4-(meth)acryloyloxydipropoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like.

[0019] Examples of the aliphatic difunctional monomer include 2-hydroxy-3-acryloyloxypropyl methacrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and glycerol di(meth)acrylate.

[0020] Examples of the trifunctional monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate.

[0021] Examples of the tetrafunctional monomer include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate.

[0022] Examples of the urethane-based polymerizable monomer include di(meth)acrylates having a bifunctional or trifunctional or higher urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group, such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, or 3-chloro-2-hydroxypropyl(meth)acrylate, with a diisocyanate compound, such as methylcyclohexane diisocyanate, methylenebis(4-cyclohexylisocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methylmethylbenzene, or 4,4-diphenylmethane diisocyanate.

[0023] There is no restriction on the use of oligomers or prepolymers having at least one polymerizable group in the molecule other than these (meth)acrylate polymerizable monomers. In addition, there is no problem even if the same molecule has a substituent such as a fluoro group. The above-described polymerizable monomers can be used alone or in combination of two or more.

[0024] <(b) Acidic group-containing polymerizable monomer> The acidic group-containing polymerizable monomer (b) contained in the dental adhesive composition of the present invention exhibits adhesive properties by interacting with the adherend, such as biological hard tissue (enamel or dentin of natural teeth). The (b) acidic group-containing polymerizable monomer that can be used in the dental adhesive composition of the present invention can be used without any restrictions as long as it is a polymerizable monomer having an acidic group. Specific examples of the acidic group that the (b) acidic group-containing polymerizable monomer has include, but are not limited to, a phosphoric acid group, a pyrophosphoric acid group, a phosphonic acid group, a carboxylic acid group, a sulfonic acid group, and a thiophosphoric acid group. The (b) acidic group-containing polymerizable monomer can be used without any restrictions in terms of the number (monofunctional group or polyfunctional group) and type of radically polymerizable unsaturated group that the (b) acidic group-containing polymerizable monomer has. Specific examples of the unsaturated group that the (b) acidic group-containing polymerizable monomer has include an acryloyl group, a methacryloyl group, a styryl group, a vinyl group, and an allyl group. Among these unsaturated groups, it is preferable that the acidic group-containing polymerizable monomer has an acryloyl group and / or a methacryloyl group.

[0025] These (b) acidic group-containing polymerizable monomers may also contain other functional groups, such as alkyl groups, halogens, amino groups, glycidyl groups, and hydroxyl groups, in the molecule, and the (b) acidic group-containing polymerizable monomers may be short main chain monomers as well as long main chain oligomers, prepolymers, etc., without any restrictions. Furthermore, derivatives of (b) acidic group-containing polymerizable monomers in which the acidic groups of the (b) acidic group-containing polymerizable monomers are partially neutralized to metal salts, ammonium salts, acid chlorides, etc., may also be used to the extent that they do not adversely affect the adhesion to various adherends.

[0026] Specific examples of the (b) acidic group-containing polymerizable monomer that can be used in the dental adhesive composition of the present invention are as follows: In this specification, (meth)acrylate or (meth)acryloyl is used to collectively refer to both acryloyl group-containing polymerizable monomers and methacryloyl group-containing polymerizable monomers. Examples of the acidic group-containing polymerizable monomer having a phosphoric acid group include (meth)acryloyloxymethyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, and 6-(meth)acryloyloxyhexyl dihydrogen phosphate. phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyheptyl dihydrogen phosphate, ) Acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyeicosyl dihydrogen phosphate, di(meth)acryloyloxyethyl hydrogen phosphate, di(meth)acryloyloxybutyl hydrogen phosphate, di(meth)acryloyloxyhexyl hydrogen phosphate, di(meth)acryloyloxyoctyl hydrogen phosphate, di(meth)acryloyloxynonyl hydrogen phosphate Examples of the polymerizable monomers include, but are not limited to, acidic group-containing polymerizable monomers such as acryloyloxyethyl phenyl phosphate, di(meth)acryloyloxydecyl hydrogen phosphate, 1,3-di(meth)acryloyloxypropyl-2-dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl 2'-bromoethyl hydrogen phosphate, and (meth)acryloyloxyethyl phenyl phosphonate.

[0027] Examples of the acidic group-containing polymerizable monomer having a pyrophosphate group include di[2-(meth)acryloyloxyethyl] pyrophosphate, di[3-(meth)acryloyloxypropyl] pyrophosphate, di[4-(meth)acryloyloxybutyl] pyrophosphate, di[5-(meth)acryloyloxypentyl] pyrophosphate, di[6-(meth)acryloyloxyhexyl] pyrophosphate, di[7-(meth)acryloyloxyheptyl] pyrophosphate, and pyrophosphate. Examples of the polymerizable monomers include, but are not limited to, acidic group-containing polymerizable monomers such as di[8-(meth)acryloyloxyoctyl] pyrophosphate, di[9-(meth)acryloyloxynonyl] pyrophosphate, di[10-(meth)acryloyloxydecyl] pyrophosphate, di[12-(meth)acryloyloxydodecyl] pyrophosphate, tetra[2-(meth)acryloyloxyethyl] pyrophosphate, and tri[2-(meth)acryloyloxyethyl] pyrophosphate.

[0028] Examples of polymerizable monomers having a carboxylic acid group include (meth)acrylic acid, 2-chloro(meth)acrylic acid, 3-chloro(meth)acrylic acid, 2-cyano(meth)acrylic acid, aconitic acid, mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, citraconic acid, utraconic acid, 1,4-di(meth)acryloyloxyethylpyromellitic acid, 6-(meth)acryloyloxynaphthalene-1,2,6-tricarboxylic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, 4-(meth)acryloyloxybutyl trimellitic acid and its anhydride, 2-(meth)acryloyloxybenzoic acid, β-(meth)acryloyloxyethyl hydrogen succinate, β-(meth) Acryloyloxyethyl hydrogen maleate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, p-vinyl benzoic acid, 4-(meth)acryloyloxyethoxycarbonyl phthalic acid, 4-(meth)acryloyloxybutyloxycarbonyl phthalic acid, 4-(meth)acryloyloxyhexyloxycarbonyl phthalic acid, 4-(meth)acryloyloxyoctyloxycarbonyl phthalic acid, 4-(meth)acryloyloxydecyloxy Examples of the polymerizable monomers include, but are not limited to, acryloyloxycarbonylphthalic acid and its acid anhydrides, 5-(meth)acryloylaminopentylcarboxylic acid, 6-(meth)acryloyloxy-1,1-hexanedicarboxylic acid, 8-(meth)acryloyloxy-1,1-octanedicarboxylic acid, 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid, and 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid.

[0029] In addition, examples of the acidic group-containing polymerizable monomer having a phosphonic acid group include, but are not limited to, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, (6-methacryloxy)hexyl phosphonoacetate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, and 10-(meth)acryloyloxydecyl-3-phosphonoacetate.

[0030] In addition, examples of the acidic group-containing polymerizable monomer having a sulfonic acid group include, but are not limited to, 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, 2-sulfoethyl (meth)acrylate, 4-(meth)acryloyloxybenzenesulfonic acid, and 3-(meth)acryloyloxypropanesulfonic acid. These acidic group-containing polymerizable monomers can be used alone or in combination.

[0031] Among these acidic group-containing polymerizable monomers, it is preferable to use 10-methacryloyloxydecyl dihydrogen phosphate, (6-methacryloxy)hexyl phosphonoacetate, 6-methacryloyloxyhexyl-3-phosphonoacetate, 4-methacryloyloxyethyl trimellitic acid and its anhydride, 4-acryloyloxyethyl trimellitic acid and its anhydride, etc.

[0032] The (a) acidic group-free polymerizable monomer and (b) acidic group-containing polymerizable monomer that can be used in the dental adhesive composition of the present invention are preferably contained in a weight ratio of (a) acidic group-free polymerizable monomer:(b) acidic group-containing polymerizable monomer=99:1 to 70:30, more preferably 95:5 to 80:20. If the weight ratio of (b) acidic group-containing polymerizable monomer is less than 1, the effect of self-adhesion to biological hard tissues (such as enamel and dentin of natural teeth) is not observed. On the other hand, if the weight ratio of (b) acidic group-containing polymerizable monomer exceeds 30, the polymerization of other polymerizable monomers is inhibited, resulting in problems such as a decrease in mechanical strength.

[0033] <(f) Acidic group-free hydrophilic polymerizable monomer> Furthermore, when the dental adhesive composition of the present invention is to be provided with high self-adhesiveness to tooth structure, it is preferable that the (a) acidic group-free polymerizable monomer further contains (f) an acidic group-free hydrophilic polymerizable monomer as a part of the (a) acidic group-free polymerizable monomer. By including (f) an acidic group-free hydrophilic polymerizable monomer, the wettability with the adherend, such as biological hard tissue (enamel or dentin of natural teeth), is improved, and thus the adhesiveness can be enhanced. In this specification, the term "acid group-free hydrophilic polymerizable monomer" refers to a polymerizable monomer having a solubility of 10 parts by weight or more in 100 parts by weight of water at 23°C, and other polymerizable monomers are defined as hydrophobic polymerizable monomers. In other words, 10 g of polymerizable monomer is added to 100 g of water kept at 23°C in a sample bottle, stirred for 10 minutes, and then left to stand. After 10 minutes, when the mixture mixed in the sample bottle is observed, the polymerizable monomer that dissolves uniformly and transparently or semi-transparently in the mixture is defined as an acid group-free hydrophilic polymerizable monomer, and the polymerizable monomer that does not dissolve is defined as a hydrophobic polymerizable monomer.

[0034] Specific examples of the (f) acidic group-free hydrophilic polymerizable monomer that can be used in the dental adhesive composition of the present invention include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1,2-dihydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2-hydroxypropyl-1,3-di(meth)acrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, pentaerythritol di(meth)acrylate, 2- Examples of suitable monomers include, but are not limited to, trimethylammonium ethyl (meth)acryl chloride, (meth)acrylamide, 2-hydroxyethyl (meth)acrylamide, polyethylene glycol di(meth)acrylate (having 9 or more oxyethylene groups), 2-hydroxy-3-acryloyloxypropyl methacrylate, 2-hydroxy-1-3-dimethacryloyloxypropane, dimethylacrylamide, acryloylmorpholine, isopropylacrylamide, diethylacrylamide, dimethylaminopropylacrylamide, and hydroxyethylacrylamide.

[0035] These (f) acid group-free hydrophilic polymerizable monomers can be used alone or in combination. Among these (f) acid group-free hydrophilic polymerizable monomers, those having a solubility of 20 parts by weight or more in 100 parts by weight of water at 23°C are preferred, and those having a solubility of 40 parts by weight or more in 100 parts by weight of water at 23°C are more preferred. Specific examples include 2-hydroxyethyl (meth)acrylate, polyethylene glycol di(meth)acrylate (having 9 oxyethylene groups), polyethylene glycol di(meth)acrylate (having 14 oxyethylene groups), polyethylene glycol di(meth)acrylate (having 23 oxyethylene groups), 2-hydroxy-3-acryloyloxypropyl methacrylate, 2-hydroxy-1-3-dimethacryloyloxypropane, dimethylacrylamide, acryloylmorpholine, isopropylacrylamide, diethylacrylamide, dimethylaminopropylacrylamide, and hydroxyethylacrylamide.

[0036] The content of the (f) hydrophilic polymerizable monomer not containing an acidic group that can be used in the dental adhesive composition of the present invention is preferably 5 to 70 parts by weight, more preferably 7 to 60 parts by weight, and even more preferably 10 to 50 parts by weight, in 100 parts by weight of the (a) polymerizable monomer not containing an acidic group. If the content of the (f) hydrophilic polymerizable monomer in the (a) polymerizable monomer not containing an acidic group exceeds 70 parts by weight, the polymerization of other polymerizable monomers may be inhibited, which may adversely affect physical properties. On the other hand, if the content of the (f) hydrophilic polymerizable monomer is less than 5 parts by weight, the wettability to biological hard tissues may be poor.

[0037] In order to impart adhesiveness to precious metals to the dental adhesive composition of the present invention, it is also effective for the present invention to use a polymerizable monomer containing a sulfur atom in the molecule. As long as the polymerizable monomer contains a sulfur atom in the molecule, it can be used without any problem regarding the type and number of unsaturated groups and the presence or absence of other functional groups.

[0038] Specific examples of polymerizable monomers containing sulfur atoms that can be used in the dental adhesive composition of the present invention include (meth)acrylates having a triazinethiol group, (meth)acrylates having a mercapto group, (meth)acrylates having a polysulfide group, (meth)acrylates having a thiophosphoric acid group, (meth)acrylates having a disulfide cyclic group, (meth)acrylates having a mercaptodiathiazole group, (meth)acrylates having a thiouracil group, (meth)acrylates having a thiirane group, etc., but are not limited thereto. These polymerizable monomers containing sulfur atoms in the molecule can be used alone or in combination.

[0039] In order to impart adhesion to ceramics, composite resins, etc. to the dental adhesive composition of the present invention, it is also effective for the present invention to use an organosilane compound having at least one polymerizable unsaturated group in the molecule. Any organosilane compound having a polymerizable unsaturated group in the molecule can be used regardless of the type and number of unsaturated groups and the presence or absence of other functional groups. These organosilane compounds can be used alone or in combination.

[0040] Specific examples of organosilane compounds having a polymerizable unsaturated group that can be used in the dental adhesive composition of the present invention include, but are not limited to, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyl(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and the like.

[0041] <(c) Filler> The (c) filler that can be used in the present invention can be a known filler that is generally used in dental composite materials. (c) fillers include inorganic fillers, organic fillers, and organic-inorganic composite fillers, and they can be used not only alone but also in combination regardless of the type of filler.

[0042] Specific examples of inorganic fillers include silica, aluminum silicate, alumina, titania, zirconia, various glasses (including fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminum silica glass, glass containing strontium or zirconium, glass ceramics, fluoroaluminosilicate glass, and synthetic glass by the sol-gel method), Aerosil (registered trademark), calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, etc. These inorganic fillers may be used as aggregates, and examples thereof include silica-zirconia composite oxide aggregates obtained by mixing silica sol and zirconia sol, spray drying and heat treatment.

[0043] Examples of organic fillers include elastomers such as polyvinyl acetate, polyvinyl alcohol, and styrene-butadiene rubber; non-crosslinkable (meth)acrylate polymers which are homopolymers of monofunctional (meth)acrylate polymerizable monomers such as polymethyl methacrylate (PMMA), polyethyl methacrylate, polypropyl methacrylate, and polybutyl methacrylate; crosslinkable (meth)acrylate polymers obtained by copolymerizing a monofunctional (meth)acrylate polymerizable monomer with a polymerizable monomer having two or more functional groups; polyvinyl acetate, polyethylene glycol, polypropylene glycol, and polyvinyl alcohol, but are not limited to these.

[0044] Examples of organic-inorganic composite fillers include, but are not limited to, fillers whose surfaces are polymerized and coated with a polymerizable monomer, fillers that are mixed and polymerized with a filler and a polymerizable monomer and then pulverized to an appropriate particle size, and fillers that are previously dispersed in a polymerizable monomer and then subjected to emulsion polymerization or suspension polymerization. These fillers can be of any shape, such as spherical, needle-like, plate-like, crushed, or scaly. The average particle size of the filler varies depending on the type of filler. In the case of inorganic fillers, fillers can be used if they are in the range of 0.01 to 20 μm, preferably in the range of 0.01 to 10 μm, and more preferably in the range of 0.01 to 5 μm. In the case of organic-inorganic composite fillers, fillers can be used if they are in the range of 0.05 to 100, preferably in the range of 0.5 to 50 μm, and more preferably in the range of 1 to 30 μm. In the case of organic fillers, there is no particular restriction on the average particle size, and fillers with average particle sizes in any range can be used. The information on the average particle size can be obtained by a laser diffraction particle size measuring device. (c) When the filler is an aggregate, the above average particle size is the average particle size of the aggregate. In addition, the average particle size of the filler is preferably 0.1 to 20 μm, and more preferably in the range of 0.1 to 10 μm. The information such as the average particle size and the coefficient of variation of the particle size can be obtained by a laser diffraction type particle size measuring instrument. (b) When the filler is an aggregate, the above average particle size is the average particle size of the aggregate. If the average particle size is less than 0.1 μm, the dental adhesive composition becomes sticky and easily contains air bubbles. If the average particle size is more than 20 μm, the surface smoothness of the dental adhesive composition after polishing decreases.

[0045] Furthermore, the surface of the filler may be multifunctionalized by a surface treatment method using a surface treatment agent, etc., and these surface-treated fillers can be used without any restrictions. Specific examples of surface treatment agents used to multifunctionalize the surface of the filler include surfactants, fatty acids, organic acids, inorganic acids, various coupling agents (titanate coupling agents, aluminate coupling agents, and silane coupling agents), metal alkoxide compounds, etc. Specific examples of surface treatment methods include a method of spraying a surface treatment agent from above while the filler is in a flowing state, a method of dispersing the filler in a solution containing a surface treatment agent, and a method of multi-layer treatment of the filler surface with several types of surface treatment agents. However, the surface treatment agents and surface treatment methods are not limited to these. In addition, these surface treatment agents and surface treatment methods can be used alone or in a complex combination.

[0046] Examples of the silane coupling agent include γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, etc. Preferably, γ-methacryloxypropyltrimethoxysilane is used. The surface treatment of the aggregate or filler may be performed with the same type of coupling agent or with a different type of coupling agent.

[0047] The content of the (c) filler that can be used in the dental adhesive composition of the present invention is not particularly limited, but is preferably 50 to 900 parts by weight, more preferably 70 to 800 parts by weight, relative to 100 parts by weight of the total content of the resin components consisting of (a) acidic group-free polymerizable monomer, (b) acidic group-containing polymerizable monomer, (d) photopolymerization initiator, and (e) chain transfer agent contained in the dental adhesive composition. If the content of the (c) filler is less than 50 parts by weight, sufficient mechanical strength cannot be obtained. In addition, the increase in the content of the (a) acidic group-free polymerizable monomer and (b) acidic group-containing polymerizable monomer increases the polymerization shrinkage, which increases the possibility of causing problems such as the formation of a contraction gap between the restoration and the cavity wall. In addition, if the content exceeds 900 parts by weight, it is difficult to obtain a dental adhesive composition in which the filler is uniformly dispersed. In addition, as the content of the filler increases, the content of the (b) acidic group-containing polymerizable monomer decreases relatively, so that the self-adhesion to the tooth structure is likely to decrease.

[0048] <(d) Photopolymerization initiator> The photopolymerization initiator (d) used in the dental adhesive composition of the present invention is not particularly limited, and any known photopolymerization initiator generally used in the dental field can be used without any limitation.

[0049] As the photopolymerization initiator, a photosensitizer, a photosensitizer / photopolymerization accelerator, etc. can be suitably used. Specific examples of the photosensitizer include α-diketones such as benzil, camphorquinone, α-naphthyl, acetonaphthene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, and naphthoquinone; benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; thioxanthones such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; benzophenones such as benzophenone, p-chlorobenzophenone, and p-methoxybenzophenone; Examples of the acylphosphine oxides include trimethylbenzoyldiphenylphosphine oxide and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1; ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, and benzyl (2-methoxyethyl ketal); and titanocenes such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, and bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium.

[0050] Specific examples of the photopolymerization accelerator include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, pN,N-dimethyl-toluidine, mN,N-dimethyl-toluidine, pN,N-diethyl-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, p-dimethylaminobenzaldehyde ... N,N-dimethyl anthranilic acid ethyl ester, p-dimethylaminobenzoic acid amino ester, N,N-dimethyl anthranilic acid methyl ester, N,N-dihydroxyethylaniline, pN,N-dihydroxyethyl-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl-α-naphthylamine, N,N-dimethyl-β-naphthylamine, tributylamine, Tertiary amines such as tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, 2,2'-(n-butylimino)diethanol, secondary amines such as N-phenylglycine, 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, Examples of suitable sulfur-containing compounds include barbituric acids such as butyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin diversatate, dioctyltin bis(mercaptoacetic acid isooctyl ester) salt, and tetramethyl-1,3-diacetoxydistannoxane; aldehyde compounds such as lauryl aldehyde and terephthalaldehyde; and sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decanethiol, and thiosalicylic acid.

[0051] Furthermore, in order to improve the photopolymerization promoting ability, it is effective to add oxycarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxyisobutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, and dimethylolpropionic acid in addition to the above-mentioned photopolymerization accelerators. These photopolymerization initiators can be used alone or in combination of two or more. Furthermore, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules, if necessary, without any problems. Furthermore, these various types of photopolymerization initiators can be used alone or in combination of two or more types, regardless of the polymerization mode or polymerization method.

[0052] The content of the (d) photopolymerization initiator may be appropriately selected from the range of 0.01 to 10 parts by weight in terms of outer percentage relative to 100 parts by weight of the total content of the polymerizable monomer components consisting of (a) acidic group-free polymerizable monomer and (b) acidic group-containing polymerizable monomer. It is preferably 0.05 to 7 parts by weight, more preferably 0.1 to 5 parts by weight. If the content of the (d) photopolymerization initiator is less than 0.01 parts by weight, the polymerizable monomer cannot be sufficiently polymerized and cured, and high mechanical properties cannot be obtained. If it is contained in excess of 10 parts by weight, the polymerization curing property for the polymerizable monomer remains unchanged, but there is a risk of discoloration and the like.

[0053] <(e) Chain transfer agent containing an α-alkylstyrene compound> The dental adhesive composition of the present invention is characterized by containing (e) a chain transfer agent containing an α-alkylstyrene compound. The effect of the present invention is manifested only when the composition contains an α-alkylstyrene compound among various chain transfer agents. When only other chain transfer agents are used, the polymerization rate, mechanical properties, and adhesion to tooth structure tend to decrease at the same time, and it is not possible to simultaneously achieve the performance required as a restorative material.

[0054] The α-alkylstyrene compound is not particularly limited and can be appropriately selected according to purpose.Specific examples include 2-phenyl-1-propene, 2,4-diphenyl-4-methyl-1-pentene, 2,4-diphenyl-4-methyl-2-pentene, 3,5-diphenyl-5-methyl-2-heptene, 3,5-diphenyl-5-methyl-3-heptene, 1,3-diphenyl-1-butene, 1,1-diphenylethylene, etc.Preferably, 2,4-diphenyl-4-methyl-1-pentene is used.

[0055] In addition, other chain transfer agents can be used in combination with the α-alkylstyrene compound as long as the effects of the present invention are not impaired, and known compounds can be used without any restrictions.Specific examples include mercaptan compounds such as n-butyl mercaptan and n-octyl mercaptan, and terpenoid compounds such as limonene, myrcene, α-terpinene, β-terpinene, γ-terpinene, terpinolene, β-pinene, and α-pinene.

[0056] The amount of the chain transfer agent containing (e) an α-alkylstyrene compound is 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the total content of the polymerizable monomers consisting of (a) an acidic group-free polymerizable monomer and (b) an acidic group-containing polymerizable monomer. If the amount of the chain transfer agent is less than 0.01 parts by weight, the internal strain generated during polymerization of the dental adhesive composition may not be sufficiently suppressed, and sufficient mechanical strength and durable adhesiveness may not be exhibited. If the amount of the chain transfer agent is more than 5 parts by weight, the chain transfer agent may inhibit polymerization and reduce curability, and the amount of unreacted polymerizable monomer remaining in the cured composition may increase, resulting in a decrease in various properties.

[0057] <Other ingredients> In addition to the above components (a) to (e), the dental adhesive composition of the present invention may contain any of the following components as required: excipients typified by fumed silica, ultraviolet absorbers such as 2-hydroxy-4-methylbenzophenone, polymerization inhibitors such as hydroquinone, hydroquinone monomethyl ether, and 2,5-ditertiarybutyl-4-methylphenol, discoloration inhibitors, antibacterial agents, coloring pigments, and other conventionally known additives. In addition, taking into consideration the permeability to the tooth structure, demineralization properties, and biological safety, water and solvents that can be mixed with water in any ratio can be added as necessary. Examples of such components include alcohols such as methanol, ethanol, and propanol, and ketones such as acetone and methyl ethyl ketone. The method of using the dental adhesive composition of the present invention is not particularly limited, and it can be used not only alone, but also in appropriate combination with other treatment materials such as etching materials, primers, bonding materials, self-etching primers, ceramic primers, metal primers, noble metal primers, bonding materials, and filling and restorative materials. Conventionally known additives and other components can be added as necessary.

[0058] Furthermore, one aspect of the present invention is that the refractive index na before curing of the resin component consisting of (a) the acidic group-free polymerizable monomer, (b) the acidic group-containing polymerizable monomer, (d) the photopolymerization initiator, and (e) the chain transfer agent, and the refractive index nc of the (c) filler satisfy the relationship of the following formula (1). |na-nc|≦0.01 (1) As a result, the dental adhesive composition of the present invention can obtain high transparency due to the positional relationship of the refractive indexes of the (c) filler and the resin component, and exhibits a deep cure depth. In this specification, a deep cure depth is defined as a photocuring depth of 3.5 mm or more, more preferably 4.0 mm or more, measured according to ISO4049.

[0059] Photopolymerization initiators and chain transfer agents are also components of the resin and have a significant effect on the refractive index, but because their content is small, the effect on the refractive index is thought to be small. However, if the content is large, it will affect the refractive index, so it is necessary to adjust the mixing ratio, etc., of not only the polymerizable monomer but also the polymerization initiator.

[0060] When a combination of multiple fillers is used as the (c) filler, the refractive index nc of the (c) filler is additive, so the refractive index of each filler can be added according to the ratio of the amounts to calculate the refractive index nc of the (c) filler. However, if the difference in refractive index between the fillers used is excessively large, the composition may become opaque and the curing depth may decrease even if the above formula (1) is satisfied. Therefore, when a combination of multiple fillers is used, it is preferable that at least 40% by weight, preferably 50% by weight, more preferably 60% by weight of the fillers in 100% by weight of the (c) filler each satisfy the above formula (1).

[0061] In addition, it is also a preferred embodiment to make the surface of the (c) filler multifunctional by a surface treatment method using a surface treatment agent, etc., and these surface-treated fillers can also be used in the dental adhesive composition of the present invention without any restrictions. In this case, there is no problem as long as the refractive index nc of the (c) filler satisfies the relationship of formula 1 based on the refractive index before the multifunctionalization by each surface treatment method.

[0062] In the dental field, various color systems are used to measure and quantify the color tone of dental materials such as tooth structure, artificial teeth, porcelain, and hard resin. One method for quantifying the opacity of dental filling materials is the contrast ratio, which uses the Y value, which relates to brightness, among the tristimulus values ​​in the XYZ color system specified in JIS Z8701. The contrast ratio is calculated by placing a disk-shaped test specimen of a certain thickness on a standard white background or a standard black background, illuminating it under certain conditions (light source, irradiation area, etc.), measuring the brightness of the white background (Yw) and the brightness of the black background (Yb), and calculating the contrast ratio from a specific formula. Since the contrast ratio is affected by the thickness of the test specimen, the contrast ratio of the dental adhesive composition of the present invention is calculated using formula (2) described in Dental Materials and Instruments Vol. 14 Special Issue 26 (1995), which includes a correction for the thickness of the test specimen in order to obtain a more accurate contrast ratio. Contrast ratio = 1-(1-Yw / Yb)^(1 / L) Equation (2) The closer the contrast ratio is to 1, the more opaque the material is, and the closer it is to 0, the more transparent the material is. In the dental adhesive composition of the present invention, when the refractive index na before curing of the resin component consisting of (a) a polymerizable monomer not containing an acidic group, (b) a polymerizable monomer containing an acidic group, (d) a photopolymerization initiator, and (e) a chain transfer agent, and the refractive index nc of (c) the filler satisfy the relationship of formula (1) above, the value of the contrast ratio before curing is 0.5 or less, more preferably 0.4 or less. When the contrast ratio of the dental adhesive composition of the present invention before curing exceeds 0.5, the transparency of the dental adhesive composition is too low, so that the photocuring depth may decrease, and the polymerization rate of the dental adhesive composition of the present invention may decrease, so that the adhesiveness may decrease.

[0063] Furthermore, in the dental adhesive composition of the present invention, when the refractive index na before curing of the resin component consisting of (a) acidic group-free polymerizable monomer, (b) acidic group-containing polymerizable monomer, (d) photopolymerization initiator, and (e) chain transfer agent and the refractive index nc of (c) filler satisfy the relationship of the above formula (1), the refractive index of the resin increases after curing, and the difference between the refractive index na and the refractive index nc of (c) filler becomes large. As a result, the composition becomes opaque after curing, and the contrast ratio value after curing is in the range of 0.4 to 0.8. The moderate opacity can mask the background color of the cavity wall, etc., and excellent aesthetics can be obtained without being affected by the background color. When the contrast ratio of the dental adhesive composition of the present invention after curing exceeds 0.8, the transparency is too low, which may impair aesthetics.On the other hand, when the contrast ratio of the dental adhesive composition after curing is less than 0.4, the transparency of the dental adhesive composition is too high, which makes it impossible to mask the background color of the cavity wall, etc., and thus causes the aesthetics to be impaired by the influence of the background color. EXAMPLES

[0064] Examples of the present invention will be specifically described below, but the present invention is not limited to these examples.

[0065] The test methods employed in the examples and comparative examples are as follows.

[0066] (1) Measurement of refractive index of filler Using tricresyl phosphate and dioctyl adipate (both manufactured by Daihachi Chemical Industry Co., Ltd.), several types of immersion liquids with arbitrary refractive indexes for refractive index measurement are prepared in advance. In a thermostatic chamber at 25°C, a small amount of filler is placed on a slide glass, and several drops of the prepared immersion liquid are dropped and mixed uniformly, and then a cover glass is placed on the slide glass to prepare a measurement sample. The refractive index of the immersion liquid at the point when the measurement sample becomes most transparent is measured and used as the refractive index of the filler. (2) Refractive index measurement of polymerizable monomers The refractive index (25°C) of the prepared resin component was measured using an Abbe refractometer (Atago Co., Ltd.: Model 2T).

[0067] (3) Opacity measurement The dental adhesive composition prepared is filled into a stainless steel mold (15φ×1mm: disk-shaped), and then a cover glass is placed from above and pressed with a glass plate. With the cover glass still attached, the test specimen is placed on a background of a standard white plate (D65 / 10°X=81.07, Y=86.15, Z=93.38) or a standard black plate (D65 / 10°X=0.0, Y=0.0, Z=0.0), and is illuminated under a certain condition (light source: C, viewing angle: 2°, measuring area: 11mm) using a color guide spectrophotometer (manufactured by BYK-Chemie Co., Ltd.), and the brightness of the white background (Yw) and the brightness of the black background (Yb) before curing are measured. Then, the cover glass was irradiated with light using a photopolymerization irradiator (Grip Light II: Matsufu) for 1 minute to cure, and the cured product was removed from the mold, and the brightness (Yw) of the white background and the brightness (Yb) of the black background after curing were measured according to the above procedure. The thickness of the test specimen was measured at 5 points using a micrometer, and the average value was taken as the test specimen thickness. From the measured values ​​of Yw, Yb and the thickness of the test specimen before and after curing thus obtained, the contrast ratio (C) of the dental adhesive composition before and after curing was calculated according to formula (2).

[0068] (4) Tooth adhesion test Extracted bovine mandibular permanent central incisors are frozen and stored within 24 hours, then thawed. The roots are removed and the crowns are cut to prepare small pieces of bovine teeth, which are then embedded in epoxy resin. The embedded bovine teeth are then polished with #600 waterproof abrasive paper under water to expose the enamel or dentin, and washed with water and dried. A double-sided tape with a hole of 4 mm diameter is applied to the exposed enamel or dentin to define the adhesive surface. A plastic mold (inner diameter 4 mm, height 2 mm or 4 mm) is fixed to the defined surface, and a dental adhesive composition is filled in the adhesive surface, and the composition is cured by irradiating light for 20 seconds using a photopolymerization irradiator (Grip Light II: manufactured by Matsukaze). The mold is then removed to prepare an adhesive test specimen. The adhesive test specimen is immersed in distilled water at 37°C for 24 hours, and then a dentin adhesion test is performed using an Instron universal testing machine (Instron 5567, manufactured by Instron) at a crosshead speed of 1 mm / min using shear adhesive strength to measure the initial adhesive strength. In addition, adhesive test specimens were prepared and immersed in distilled water at 37°C for 24 hours, after which 2,000 thermal cycles were applied to perform a tooth adhesion test, and the results were recorded as durable adhesive strength.

[0069] (5) Bending strength The dental adhesive composition thus prepared was filled into a stainless steel mold, cover glass was placed on both sides, and the composition was pressed against a glass plate. Then, the composition was irradiated with light for 10 seconds at 5 locations using a photopolymerization irradiator (Blue Shot, manufactured by Matsukaze) to harden the composition. After hardening, the hardened product was removed from the mold, and the back side was irradiated with light in the same manner to obtain a test specimen (25×2×2mm: rectangular parallelepiped type). The test specimen was immersed in water at 37°C for 24 hours, and then a bending test was performed. The bending test was carried out using an Instron universal testing machine (Instron 5567, manufactured by Instron Corporation) with a support distance of 20 mm and a crosshead speed of 1 mm / min. The test was carried out on 10 specimens, and the average value was used for evaluation. (6) Polymerization shrinkage stress A metal primer was applied to an iron plate (material: SPCC, inner diameter: 10 mm, thickness: 1 mm) with a strain gauge (Kyowa Denko, KFG-2-120-C1-11) attached thereto, and the plate was then placed in a ring-shaped mold made of fluororesin (inner diameter: 10 mm, thickness: 2 mm), and a dental adhesive composition was filled to a thickness of 1 mm on the primer-coated surface. Light was irradiated from above, and the distortion of the iron plate due to hardening was measured. The polymerization shrinkage stress was calculated by multiplying the distortion values ​​600 seconds and 24 hours after light irradiation by the elastic modulus of the iron plate based on the following formula (3). Polymerization shrinkage stress (MPa) = ε x E···Equation (3) ε: distortion E: Elastic modulus

[0070] (7) Polymerization rate The infrared absorption spectrum of the prepared dental adhesive composition was measured by the KBR method using an infrared absorption spectrometer (JASCO FT-IR-6300, manufactured by JASCO Corporation) (measurement range: 400 to 4000 cm-1). The peak heights (h) attributable to the (meth)acrylate double bond (1637 cm-1) and carbonyl group (1717 cm-1) of the dental adhesive composition before curing were measured. The relative amount of unpolymerized monomer in each material was determined by the ratio (Ib) of the peak heights before curing of the double bond (1637 cm-1) / carbonyl group (1717 cm-1). Thereafter, the dental adhesive composition was irradiated with light for 10 seconds using a photopolymerization irradiator (Blue Shot, manufactured by Matsukaze) to be cured. The peak heights (h) attributable to the (meth)acrylate double bond (1637 cm-1) and carbonyl group (1717 cm-1) were measured immediately after irradiation and after 24 hours according to the above procedure, and the ratio of peak heights after curing (Ia) was calculated. The polymerization rate (%) immediately after irradiation and after 24 hours was calculated from the obtained ratio of peak heights before and after curing according to the following formula (4). Polymerization rate (%)=100- Ia / Ib x 100...Formula (4) (8) Photocuring depth The dental adhesive composition thus prepared was filled into a stainless steel mold of φ4 mm×12 mm, cover glass was placed on both sides, and the composition was pressed against a glass mixing plate, after which the composition was irradiated with light for 10 seconds each using a photopolymerization irradiator (Blue Shot: manufactured by Matsukaze) to harden the composition. After hardening, the hardened product was removed from the mold, and the unpolymerized paste was removed with a plastic spatula. The thickness of the hardened product was measured with a micrometer, and the value obtained by dividing the thickness by half was taken as the photocuring depth (mm).

[0071] The materials used in the examples and comparative examples and their abbreviations are shown below. [Polymerizable monomer (a) containing no acidic group] Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (refractive index before curing: 1.552) ·UDMA: N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)ethanol]methacrylate (Refractive index before curing: 1.483) 3G: Triethylene glycol dimethacrylate (refractive index before curing: 1.460) [Acidic group-containing polymerizable monomer (b)] 6-MHPA: (6-methacryloxy)hexylphosphonoacetate (refractive index before curing: 1.473) 10-MDP: 10-methacryloyloxydecyl dihydrogen phosphate (refractive index before curing: 1.468) [Acidic group-free hydrophilic polymerizable monomer (f)] HEMA: 2-hydroxyethyl methacrylate (refractive index before curing: 1.451) 701A: 2-hydroxy-3-acryloyloxypropyl methacrylate (refractive index before curing: 1.471) [Filler (c)] The refractive index and average particle size of the filler inorganic particles 1 to 3 used in the preparation of the dental adhesive composition were measured, and the results are shown in Table 1. These inorganic particles were appropriately silane-treated before use in the preparation of the dental adhesive composition.

[0072] [Table 1]

[0073] [Polymerization initiator (d)] ·CQ: α-camphorquinone ·DMABE: Ethyl N,N-dimethylaminobenzoate [Chain transfer agent (e)] α-MSD: 2,4-diphenyl-4-methyl-1-pentene DMH: 3,5-diphenyl-5-methyl-2-heptene Gamma terpinene ·TEMPO: 2,2,6,6-tetramethylpiperidine 1-oxyl free radical [Preparation of resin components (I1-I21)] Resin components (I1 to I21) were prepared according to the compositions shown in Table 2.

[0074] [Table 2]

[0075] [Preparation of dental self-adhesive restorative materials] Using the resin components shown in Table 2, dental self-adhesive restorative materials (Examples 1 to 17 and Comparative Examples 1 to 6) were prepared according to the compositions shown in Table 3.

[0076] [Table 3]

[0077] The suitability for formula 1 was evaluated from the relationship in the refractive index of the filler and resin component contained in the dental self-adhesive restorative materials (Examples 1 to 17 and Comparative Examples 1 to 6). The results are shown in Table 4. |na-nc|≦0.01 (1)

[0078] [Table 4]

[0079] The evaluation results for the dental self-adhesive restorative materials of Examples 1 to 17 and Comparative Examples 1 to 6 are shown in Tables 5 and 6.

[0080] [Table 5]

[0081] [Table 6]

[0082] [Examples 1 to 17] The dental self-adhesive restorative materials of Examples 1 to 17 had a low polymerization rate immediately after light irradiation, but an increase in the polymerization rate was observed after 24 hours. In addition, the polymerization shrinkage stress was low both after 600 seconds and after 24 hours, and the bending strength was also high. In other words, it is possible to effectively delay the gel point at the beginning of polymerization without inhibiting the final polymerization rate by containing an α-alkylstyrene compound as a chain transfer agent, and as a result, it is found that both low polymerization shrinkage stress and good bending strength are achieved. Furthermore, the durable adhesive strength to dentin and enamel was also high, and it was confirmed that the material has stable self-adhesion to tooth structure. Furthermore, the dental self-adhesive restorative materials of Examples 1 to 5, 8 to 12, and 14 to 17, which conform to formula (1) and have high transparency before hardening, have a photocuring depth of 4 mm or more, and it was found that the adhesive strength to dentin and enamel does not decrease even when the thickness is 4 mm.

[0083] Comparative Example 1 Since the dental self-adhesive restorative material of Comparative Example 1 does not contain a chain transfer agent, it was found that the polymerization rate immediately after light irradiation was high and the polymerization shrinkage stress was also high. In addition, although the adhesive strength to dentin and enamel was initially adhesive, the test specimen fell off in the durability test and the adhesiveness decreased.

[0084] Comparative Example 2 The dental self-adhesive restorative material of Comparative Example 2 contains an α-alkylstyrene compound as a chain transfer agent but does not contain an acidic group-containing polymerizable monomer, and therefore exhibits low polymerization shrinkage stress but has no adhesion to tooth structure.

[0085] [Comparative Examples 3 to 6] The dental self-adhesive restorative materials of Comparative Examples 3 to 6 contain a chain transfer agent other than an α-alkylstyrene compound, and have a low effect of suppressing the polymerization rate immediately after light irradiation. When γ-terpinene of Comparative Examples 3 and 4 is used, the polymerization shrinkage stress is reduced 600 seconds after light irradiation, but increases after 24 hours, and bending strength also tends to decrease. In addition, the dental self-adhesive restorative materials of Comparative Examples 3 to 6 have significantly low adhesive strength to dentin and enamel, and it was found that the test specimens frequently fell off in the durability adhesion test. In the above explanation, a one-paste type dental self-adhesive restorative material has been described, but the present invention can of course also be applied to a dental adhesive composition in which two or more pastes or liquids are mixed. [Industrial Applicability]

[0086] According to the present invention, it is possible to provide a one-paste type dental adhesive composition which has the mechanical properties and aesthetics required of a restorative material, has excellent durable adhesive strength to tooth structure, is less susceptible to the effects of polymerization shrinkage stress even when filled and cured all at once, and exhibits good durable adhesive properties.

Claims

1. (a) an acidic group-free polymerizable monomer, (b) acidic group-containing polymerizable monomer, (c) filler; (d) a photopolymerization initiator, (e) a chain transfer agent, In a dental adhesive composition comprising: (e) the chain transfer agent comprises an α-alkylstyrene compound; (d) A one-paste type dental adhesive composition characterized in that it contains only a combination of a photosensitizer (excluding the case where the photosensitizer is a photoacid generator) and a photopolymerization accelerator as a photopolymerization initiator.

2. 2. The dental adhesive composition according to claim 1, comprising (a) the acidic group-free polymerizable monomer and (b) the acidic group-containing polymerizable monomer in a weight ratio of (a) the acidic group-free polymerizable monomer:(b) the acidic group-containing polymerizable monomer=99:1 to 70:

30.

3. For 100 parts by weight of the polymerizable monomer component consisting of (a) an acidic group-free polymerizable monomer and (b) an acidic group-containing polymerizable monomer, (d) Photopolymerization initiator: 0.01 to 10 parts by weight (e) Chain transfer agent: 0.01 to 5 parts by weight and (a) an acidic group-free polymerizable monomer, (b) an acidic group-containing polymerizable monomer, (d) a photopolymerization initiator, and (e) a chain transfer agent, for 100 parts by weight of the resin component. (c) Filler: 50 to 900 parts by weight The dental adhesive composition of claim 2 comprising:

4. The dental adhesive composition according to any one of claims 1 to 3, comprising 5 to 70 parts by weight of (f) an acidic group-free hydrophilic polymerizable monomer per 100 parts by weight of (a) an acidic group-free polymerizable monomer.

5. 5. The dental adhesive composition according to claim 1, wherein the chain transfer agent (e) is 2,4-diphenyl-4-methyl-1-pentene.

Citation Information

Patent Citations

  • Adhesive material for dental use

    JP2007119404A

  • Low stress flowable dental composition

    JP2009539861A

  • Adhesive dental restoration material having decreased polymerization contraction force

    JP2012171885A

  • Dental restoration kit

    JP2014231493A

  • Curable dental composition comprising particles with different refractive index

    JP2015067594A